Drugs repurposing for COVID-19: phase III clinical trial evaluation - Woro Rukmi Pratiwi (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2021)
World Health Organization (WHO) has announced coronavirus disease 2019 (COVID-19) as a global pandemic which is the largest public health crisis in this century. The spread of COVID-19 is still not well-controlled even become global health threat. As new disease, the specific drugs for COVID-19 have not been available, yet. Face of this condition, repurposing existing drugs become the best options in order to meet the urgently need of the effective drugs. In this article, the clinical trial results of some drugs for the treatment of COVID-19 included hydroxychloroquine, chloroquine, lopinavir/ritonavir, remdesivir, oseltamivir, favipiravir, and corticosteroids were reviewed. Hydroxychloroquine, choloquine and lopinavir/ritonavir were shown to be ineffective. Therefore, they were excluded from the list of drugs for the tratment of COVID-19 by WHO and the National Agency of Drug and Food Control of Republic of Indonesia (NCDE NA-DFC RI). Furthermore, NA-DFC RI has issued an emergency use authorization (EUA) for the use of remdesivir and favipiravir for the treatment of COVID-19.